The memory unsatisfied in Estrella distante of Roberto Bolaño - Susana Florinda Ramírez (Estudios de Teoría Literaria, 2015)
This article sets up to examine the fictional strategies appointed  to shape the complexity of the memory processes in there composition of a traumatic experience. Estrella distante (1996), discusses the identity of the subject and, consequently, questions the supposed transparency of testimonies. Critical memory opens the past to uninterrupted interpretations in order to prevent the crystallization of a solesense of facts.